Diastolic Dysfunction in Systemic Sclerosis: Risk Factors and Impact on Mortality. Issue 5 (30th March 2022) - Hinze, Alicia M.; Perin, Jamie; Woods, Adrianne; Hummers, Laura K.; Wigley, Fredrick M.; Mukherjee, Monica; Shah, Ami A.
Abstract : Objective: To determine the independent risk factors for diastolic dysfunction (DD) in patients with systemic sclerosis (SSc) and to evaluate the impact of DD on mortality. Methods: SSc patients enrolled in the Johns Hopkins Scleroderma Center Cohort between November 1, 2006 and November 1, 2017 with ≥1 analyzable 2‐dimensional (2‐D) echocardiogram in our system were included (n = 806). DD risk factors and SSc disease characteristics were prospectively obtained, and the presence or absence of DD was determined using the most recent 2‐D echocardiogram. Logistic regression models examined associations between clinical risk factors and DD, and Cox proportional hazards models were used to assess survival. Results: DD was present in 18.6% of participants. The majority of participants were female (84%) with a median age of 58.4 years (interquartile range 48.8–68.1). Older age (odds ratio [OR] 1.12 [95% confidence interval (95% CI) 1.09–1.15], P  < 0.001), coronary artery disease (OR 3.69 [95% CI 1.52–8.97], P  = 0.004), obesity (OR 4.74 [95% CI 2.57–8.74], P  < 0.001), longer SSc disease duration (OR 1.04 [95% CI 1.01–1.06], P  = 0.004), diffusing capacity for carbon monoxide ≤60% of predicted (OR 2.41 [95% CI 1.40–4.16], P  = 0.002), and history of scleroderma renal crisis (OR 3.18 [95% CI 1.12–9.07], P  = 0.031) were all independently associated with an increased risk of DD. Anti–Scl‐70 positivity (OR 0.49 [95% CI 0.26–0.93], P  = 0.03) and severe gastrointestinal disease (OR 0.48 [95% CI 0.30–0.79], P  = 0.004) were associated with a reduced risk of DD. The presence of DD was independently associated with an increase in the risk of mortality (hazard ratio 1.69 [95% CI 1.07–2.68], P  = 0.027). Conclusion: DD is independently associated with an increased risk of mortality in patients with SSc. Potentially modifiable risk factors, including coronary artery disease and obesity, should be addressed in patients with SSc to reduce mortality risk.